A brief discussion on the trends of habilitating technologies for Industry 4.0 and Smart manufacturing. (January 2018) - Ahuett-Garza, H.; Kurfess, T.
Highlights: The most important habilitating technologies for Industry 4.0 and Smart Manufacturing are presented. Trends are discussed. Basic concepts are defined to contextualize further discussion. Abstract: Industry 4.0 refers to the integration of a multiplicity of technologies and agents for the common goal of improving the efficiency and responsiveness of a production system. This integration has the potential to revolutionize the manner in which business are planned and conducted. Smart Manufacturing represents the implementation of Industry 4.0 on the manufacturing floor. The Internet of Things, Big Data, Cyber Physical Systems, Machine Learning, Additive Manufacturing, and Robotics are only some of the elements that are associated with this revolution. This article discusses trends in some of the habilitating technologies of Industry 4.0.